Isolasi bakteri resisten merkuri pada urin pasien dengan tumpatan amalgam di Puskesmas Tikala Baru - Kepel, Regina E.M.; Fatimawali, .; Budiarso, Fona (e-Biomedik, 2016)
Abstract: Mercury, a heavy metal, can be toxic to human body if it is exposed in high concentration. This metal has been used as dental amalgam fillings in dentistry since 150 years ago to reconstruct decayed teeth. Due to continuous exposure of mercury, bacteria inside human body have evolved mechanism of resistance toward higher form of mercury, due to the mer operon that has been charactherized in the plasmid. This study was aimed to find out whether there were mercury-resistant bacteria isolated from the urine of patients with dental amalgam fillings at Puskesmas (Primary health care) Tikala Baru, and identify the mercury-resistant bacteria. This was a descriptive exploratory study. Samples were mercury-resistant bacterial strains in the urine of patients with dental amalgam fillings who visited Puskesmas Tikala Baru. The results of mercury-resistant test showed that there were mercury-resistant bacteria in every concentrations. The morphological, physiological, and biochemical tests obtained 7 mercury-resistant bacterial genus, as follows: Streptococcus, Staphylococcus, Hafnia, Klebsiella, Enterobacter, Escherichia, and Bacillus. Conclusion: There were 7 genus of mercury-resistant bacteria which identified from urine of patient with dental amalgam fillings.Â Keywords: amalgam, mercury resistant bacteria.Â Abstrak: Merkuri merupakan suatu logam berat yang dapat bersifat toksik bila terpapar dengan tubuh manusia dalam konsentrasi tinggi. Penggunaan merkuri dalam amalgam telah digunakan dalam bidang kedokteran gigi selama hampir 150 tahun untuk merekonstruksi gigi berlubang. Akibat adanya paparan merkuri secara terus menerus, bakteri dalam tubuh manusia telah mengevolusi mekanisme resisten terhadap bentuk merkuri yang lebih tinggi di lingkungan, disebabkan oleh mer operon yang terkandung dalam plasmid. Penelitian ini bertujuan untuk mengetahui apakah terdapat bakteri resisten merkuri yang diisolasi dari urin pasien dengan tambalan merkuri di Puskesmas Tikala Baru, serta mengidentifikasi jenis dari bakteri resisten merkuri tersebut. Jenis penelitian ialah deskriptif eksploratif. Sampel yang digunakan ialah koloni bakteri yang resisten terhadap merkuri, yang terdapat dalam urin pasien dengan amalgam yang berkunjung ke Puskesmas Tikala Baru. Dari hasil uji resistensi merkuri, terdapat bakteri resisten merkuri pada setiap konsentrasi. Setelah dilakukan uji morfologi, fisiologi, dan biokimia didapatkan 7 genus bakteri yang resisten terhadap merkuri, yaitu Streptococcus, Staphylococcus, Hafnia, Klebsiella, Enterobacter, Escherichia, dan Bacillus. Simpulan: Terdapat 7 genus bakteri resisten merkuri yang teridentifikasi dalam urin pasien dengan tumpatan amalgam di Puskesmas Tikala Baru. Kata kunci: amalgam, bakteri resisten merkuri